Restorative and orthodontic interdisciplinary management of an adult patient using modified Hawley appliance: a case report (Nigerian Dental Journal, 2012)
This report presents a case of an adult female patient who had undergone orthodontic treatment to correct her malocclusion was referred to the Restorative Dentistry Clinic at the time when her brackets were due for debonding. The patient had presented with spacing of the anterior segments of both upper and lower arches with the upper canines in crossbite. At the end of the orthodontic correction of the occlusion the patient was referred to the restorative dentist for replacement of missing molars in the upper and lower arches. Fixed bridge prosthesis, implant-retained crowns or removable dentures were the treatment options for tooth replacement. Due to financial challenges the first two options were unavailable to the patient. The need to wear retainers made it impractical for the patient to be provided the third option of removable dentures. A modified design of Hawley retainers was then made for the patient that had pink acrylic bases and acrylic stock teeth to replace missing teeth. Thus, the functions of retainer and removable denture were combined in one appliance. The modified Hawley appliance designed for the patient in this study is a typical example of interdisciplinary management by the restorative dentist and the orthodontist to give appropriate care to the adult orthodontic patient.